Clinical Impact of Infection with Pandemic Influenza (H1N1) 2009 Virus in Naïve Nucleus and Multiplier Pig Herds in Norway. (22nd December 2011) - Grøntvedt, Carl Andreas; Er, Chiek; Gjerset, Britt; Germundsson, Anna; Framstad, Tore; Brun, Edgar; Jørgensen, Anne; Lium, Bjørn
Abstract : The Norwegian pig population has been free from influenza viruses until 2009. The pandemic influenza outbreak during the autumn 2009 provided an opportunity to study the clinical impact of this infection in an entirely naïve pig population. This paper describes the results of a case-control study on the clinical impact of pandemic influenza (H1N1) 2009 infection in the nucleus and multiplier herds in Norway. The infection spread readily and led to seroconversion of 42% of the Norwegian nucleus and multiplier herds within a year. Positive and negative herds were identified based on surveillance data from the Norwegian Veterinary Institute. Telephone interviews were conducted with pig herd owners or managers between November 2010 and January 2011. Pigs with clinical signs were reported from 40% of the case herds with varying morbidity and duration of respiratory disease and reduced reproductive performance. Clinical signs were reported in all age groups.